KESADARAN GENERASI Z TERHADAP PELESTARIAN MEMORI KOLEKTIF BANGSA - Rosa Salsabila Sari; Aurea Chiara Yaffa; Nabila Qurrotu Aini; Safa Yulinda; Ni Kadek Pudja Sastra; Aliesa Vebtia Azhari (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2026)
A nation’s collective memory is a shared heritage preserved in archives, whether in the form of documents, ancient manuscripts, cultural works, or historic buildings. Archives serve as the foundation of national identity and a source of knowledge for future generations. In the digital age, Generation Z as a generation that has grown up with technology has great potential in the preservation of collective memory, yet they may not necessarily possess sufficient awareness, as their attention is more focused on entertainment content. This study aims to describe Generation Z’s awareness regarding the preservation of the nation’s collective memory through three main indicators: knowledge, attitude, and action. This study employs a quantitative descriptive approach. The research was conducted at Airlangga University with a population of active students aged 18–25 years. The results indicate that Generation Z’s knowledge regarding the nation’s collective memory is quite good, their attitudes are generally positive and supportive of preservation, yet concrete actions still need improvement, particularly regarding the consistency of accessing historical content. The primary challenge faced is a lack of engaging information and outreach. This study concludes that creative communication strategies based on social media, as well as increased access to digital and physical archives, are needed so that Generation Z’s awareness can be transformed into active participation in the preservation of the nation’s collective memory.